Prevalence of higher-grade dysplasia in persistently high-risk human papillomavirus positive, cytology negative women after introduction of the new cervical cancer screening in Germany: original paper - Berger, Laura; Wolf-Breitinger, Maja; Weiß, Christel; Tuschy, Benjamin; Berlit, Sebastian; Sütterlin, Marc; Spaich, Saskia (Cancer causes & control, 2023)
According to the recently implemented organized cervical cancer screening program in Germany, women older than 35 years with negative cytology but persistent high-risk human papilloma virus (hrHPV) infection > 12 months should be referred to colposcopy for further evaluation. This study aimed to present and dissect colposcopic and histopathological findings with particular focus on associated hrHPV genotypes.
Online veröffentlicht: 28. Februar 2023
Gesehen am 22.05.2024